Production of curcuminoids from tyrosine by a metabolically engineered Escherichia coli using caffeic acid as an intermediate - Rodrigues, Joana Lúcia Lima Correia (2015)
Curcuminoids are phenylpropanoids with high pharmaceutical potential. Herein, we report an engineered artificial pathway in Escherichia coli to produce natural curcuminoids through caffeic acid. Arabidopsis thaliana 4-coumaroyl-CoA ligase (4CL1) and Curcuma longa diketide-CoA synthase (DCS) and curcumin synthase (CURS1) were used to produce curcuminoids and 70 mg/L of curcumin was obtained from ferulic acid. Bisdemethoxycurcumin and demethoxycurcumin were also produced, but in lower concentrations, by feeding p-coumaric acid or a mixture of p-coumaric acid and ferulic acid, respectively. Additionally, curcuminoids were produced from tyrosine through the caffeic acid pathway. To produce caffeic acid, tyrosine ammonia lyase (TAL) from Rhodotorula glutinis and 4-coumarate 3-hydroxylase (C3H) from Saccharothrix espanaensis were used. Caffeoyl-CoA 3-O-methyltransferase (CCoAOMT) from Medicago sativa was used to convert caffeoyl-CoA to feruloyl-CoA. Using caffeic acid, p-coumaric acid or tyrosine as a substrate, 3.9 mg/L, 0.3 mg/L and 0.2 mg/L of curcumin were produced, respectively. This is the first time DCS and CURS1 were used in vivo to produce curcuminoids and that curcumin was produced by feeding tyrosine. We have shown that curcumin can be produced using a pathway through caffeic acid. This alternative pathway represents a step forward in the heterologous production of curcumin using E. coli.